Malignant cell-specific CXCL14 promotes tumor lymphocyte infiltration in oral cavity squamous cell carcinoma. Issue 2 (21st September 2020) - Parikh, Anuraag; Shin, JuneHo; Faquin, William; Lin, Derrick T; Tirosh, Itay; Sunwoo, John B; Puram, Sidharth V
Abstract : Objectives: To explore lymphocyte infiltration as a potential mechanism behind CXCL14-mediated tumor growth suppression in oral cavity squamous cell carcinoma (OSCC). Methods: We analyzed single cell RNA-sequencing (scRNA-seq) data from OSCC to identify expression changes among malignant cells in lymph nodes (LN) versus primary tumors. CXCL14 expression in murine OSCC cell lines was quantified using qRT-PCR. Short hairpin RNA knockdown of CXCL14 was performed in mouse oral cavity (MOC)1 cells, and CXCL14 overexpression was performed in MOC2 cells. Cells in each condition were injected into C57BL/6 mice with and without T cell depletion, and tumor volume was measured. At 30 days, tumors were dissociated and analyzed by flow cytometry for CD45 + CD3 + T cells. CXCL14 expression was correlated with gene expression signatures of tumor infiltrating lymphocytes (TIL) in scRNA-seq data, as well as TCGA tumors. Results: scRNA-seq revealed CXCL14 as the most significantly downregulated gene among malignant cells in LNs relative to primary tumor, supporting a role in preventing invasion and/or metastasis. In a murine immunocompetent model, CXCL14 expression was higher in indolent MOC1 cells than in more aggressive MOC2 cells. Tumor growth in vivo was significantly increased by CXCL14 knockdown in MOC1 cells relative to control, with a corresponding decrease in TIL. In MOC2 cells, tumor growth was significantly reduced by CXCL14 overexpression relative to control and TIL were increased. Both effects were lost with T cell depletion. In a human tumor scRNA-seq cohort, we found that only malignant cell CXCL14, but not non-malignant cell or fibroblast CXCL14, was associated with TIL. Bulk CXCL14 from the TCGA cohort had no association with TIL. Conclusions: Higher CXCL14 expression by tumor cells is associated with reduced tumor growth and increased TIL, supporting immune-mediated suppression of tumor growth in OSCC. Given that CXCL14 is downregulated in LN metastases compared with primary tumors, our data raise the possibility that CXCL14-mediated immune infiltration may discourage invasion and metastasis. In human scRNA-seq data, only malignant cell-specific CXCL14 was associated with TIL, suggesting a critical context-dependent effect of CXCL14 expression.